Exploring immobilization strategies of antimicrobial peptides onto MAO-treated titanium to fight MRSA colonization and preserve osteogenic activity - Costa, Natália De Araújo Da; Monteiro, Cláudia; Grenho, Liliana; Ribeiro, Ana R.; Leiro, Victoria; Fernandes, Maria Helena; Lisboa Filho, Paulo Noronha; Martins, M. Cristina L. (Elsevier, 2026)
Alternative therapies to systemic antibiotics are increasingly explored to prevent infections associated with bone implants. Among them, the surface functionalization of titanium with antimicrobial peptides (AMP) is particularly promising due to their broad-spectrum activity and low risk of inducing bacterial resistance. However, a critical challenge remains in achieving both effective antibacterial action and the promotion of osseointegration. This proof-of-concept study investigates different strategies for immobilizing AMP onto bioactive micro-arc oxidation (MAO) coatings on titanium, aiming to combat methicillin-resistant Staphylococcus aureus (MRSA) colonization while preserving the osseointegration potential of MAO surfaces. The peptide MSI-78 was immobilized either by physical adsorption or covalent grafting, using 1,1′-carbonyldiimidazole (CDI) coupling agent or poly(ethylene glycol) (PEG) spacer. All immobilization strategies preserved the heterogeneous porous architecture and calcium/phosphorus doping of the complex MAO coatings. Prior to bacterial incubation, the surfaces were pre-conditioned with human plasma proteins. MSI-78, whether by physical adsorption or covalent grafting, killed MRSA after 5 h, but also promoted bacterial adhesion to the surface. In contrast, the combined strategy of grafted PEG and physically adsorbed AMP promoted a remarkable antibacterial effect, by reducing MRSA colonization and killing about 80% of adherent bacteria. Regardless of the immobilization strategy, bacterial killing appeared to occur via contact-mediated membrane disruption. Moreover, these PEGylated MAO surfaces with adsorbed AMP maintained excellent cytocompatibility with bone-like cells and supported osteogenic response, underscoring their potential as bioactive coatings for titanium implants.
Exploring immobilization strategies of antimicrobial peptides onto MAO-treated titanium to fight MRSA colonization and preserve osteogenic activity
Keywords: Titanium; Micro-arc oxidation; Antimicrobial peptides immobilization; Surface functionalization; Methicillin-resistant Staphylococcus aureus; Bone-like cells